Keunggulan Komparatif Buku Pelajaran IPA SMP Berbasis Penalaran Untuk Meningkatkan Hasil Belajar Siswa - I Wayan Redhana; Nyoman Diah Bestari (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2017)
This study was aimed to describe and explain (1) differences of students’ learning achievement using argument-based-science-textbook and curriculum 2013-science-textbook for junior high school. Type of the study was quasi experiment with nonequivalent pretest-postest control group design. Population of the study was the seventh grade students of SMP Negeri 4 Singaraja having 11classes. Samples of the study were chosen by cluster random sampling techniques. The sampling produced two parallel classes, that was class VIIA1 and VIIA2 and both were lotteried to determinea control and an experimental class.Results of the lottery were class VIIA1 as the control class, whereas class VIIA2 as the experimental class. The experimental class was taught using argument-based-science textbook, whereas the control class was taught using curriculum 2013-science-textbook. Results of the study showed that the average score of learning achievement of the experimental class was significant difference from the average score of learning achievement of the control class. From the average scores, it could be concluded that the average score of learning achievement of the experimental class was higher than that of the control class.